Top Management, and Relational Capital, "Consumer Decision-Making in Eastern Fast Food: An Urban Surabaya Perspective on Perceived Value and Behavioral Intent - Adi Suroso; Yeni Ika Pratiwi; Mahjudin Mahjudin (Journal of Managerial Sciences and Studies, 2025)
This study aims to examine: (1) the influence of perceived value on behavioral intentions; (2) the influence of perceived value on consumer satisfaction; (3) the influence of consumer satisfaction on behavioral intentions; and (4) the mediating role of consumer satisfaction in the relationship between perceived value and behavioral intentions. The research population comprises all customers of Surabaya Urban Area. A total of 100 respondents were selected using a convenience sampling technique. Data were collected using a structured questionnaire, and instrument validity and reliability were assessed accordingly. Hypotheses were tested through path analysis, with data processing conducted using the SPSS software. The findings indicate that: (1) perceived value significantly affects behavioral intentions; (2) perceived value significantly influences consumer satisfaction; (3) consumer satisfaction significantly affects behavioral intentions; and (4) consumer satisfaction mediates the relationship between perceived value and behavioral intentions. The study concludes that all proposed hypotheses are empirically supported.